Pendidikan: Kunci Emas Pembangunan Peradaban Indonesia - Praditiyo Ikhram (Madaris: Jurnal Guru Inovatif, 2023)
Education plays a crucial role as the key to unlocking progress for the civilization of Indonesia. This research is focused on Mts Negeri 20 East Jakarta to discuss various aspects of the education system implemented in the school, including infrastructure, teacher qualifications, and teaching methods. The research methodology involves collecting data through questionnaires, which are then analyzed to understand the students' level of comprehension of the subjects, their perception of teaching quality, and the impact of the school environment on the effectiveness of education at MTs Negeri 20 East Jakarta. The discussion of the research results includes the interpretation of data and its correlation with the concept of civilization development. Emphasis is placed on how the improvement of education quality can shape students' character, enhance intellectual capacity, and positively contribute to the progress of Indonesian civilization. In conclusion, this research provides practical and implementable recommendations to enhance the quality of education at MTs Negeri 20 East Jakarta, aligning with the main goal of this research, which is to make education the golden key to the development of the Indonesian civilization Abstrak Pendidikan memiliki peran krusial sebagai kunci pembuka menuju kemajuan peradaban Indonesia. Penelitian ini difokuskan pada Mts Negeri 20 Jakarta Timur untuk mendiskusikan aspek-aspek sistem pendidikan yang diimplementasikan di sekolah tersebut, termasuk infrastruktur, kualifikasi guru, dan metode pengajaran. Metode penelitian melibatkan pengumpulan data melalui kuesioner, yang kemudian dianalisis untuk memahami tingkat pemahaman siswa terhadap materi pelajaran, persepsi terhadap kualitas pengajaran, dan dampak lingkungan sekolah terhadap efektivitas pendidikan di MTs Negeri 20 Jakarta Timur. Pembahasan hasil penelitian melibatkan interpretasi data dan hubungannya dengan konsep pembangunan peradaban. Penekanan diberikan pada bagaimana peningkatan kualitas pendidikan dapat membentuk karakter siswa, meningkatkan kapasitas intelektual, dan memberikan kontribusi positif terhadap kemajuan peradaban Indonesia. Sebagai hasil akhir, penelitian ini menyajikan rekomendasi praktis dan implementatif untuk meningkatkan kualitas pendidikan di MTs Negeri 20 Jakarta Timur, sejalan dengan tujuan utama penelitian ini, yaitu menjadikan pendidikan sebagai kunci emas pembangunan peradaban Indonesia